2021
DOI: 10.1021/acsomega.1c05119
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Role of Cu(II) Ions on Protein Aggregation Using Two Model Proteins

Abstract: Copper is an essential trace element for human biology where its metal dyshomeostasis accounts for an increased level of serum copper, which accelerates protein aggregation. Protein aggregation is a notable feature for many neurodegenerative disorders. Herein, we report an experimental study using two model proteins, bovine serum albumin (BSA) and human serum albumin (HSA), to elucidate the mechanistic pathway by which serum albumins get converted from a fully folded globular protein to a fibril and an amorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…6A , B, E, and F) that supports existing literature. 12 , 90 , 93 In both cases, we observed that GHK could prevent and reverse aggregation of metal ion–induced BSA aggregation. Since aggregation can be rapidly reversed upon the addition of a chelator, the Zn 2+ and Cu 2+ ions do not seem to induce any permanent aggregation.…”
Section: Resultsmentioning
confidence: 69%
“…6A , B, E, and F) that supports existing literature. 12 , 90 , 93 In both cases, we observed that GHK could prevent and reverse aggregation of metal ion–induced BSA aggregation. Since aggregation can be rapidly reversed upon the addition of a chelator, the Zn 2+ and Cu 2+ ions do not seem to induce any permanent aggregation.…”
Section: Resultsmentioning
confidence: 69%
“…Due to their ability to interact with hydrophobic regions in protein secondary structures, they disrupt the natural tendency of selected proteins to form oligomers by stacking β-sheet structures [ 46 ]. Aggregation and fibrillation of proteins controlled by nanomaterials can contribute to a change in the behavior of proteins, which is expressed in a change in fluorescence intensity or a shift in the fluorescence emission from some NPs as a result of interaction with proteins [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, understanding the precise impact of cations on protein aggregation remains a challenge, and further research is needed to establish a consensus. 37,111,113,114…”
Section: Aggregation In Protein-based Therapeutic Productsmentioning
confidence: 99%